2018
DOI: 10.1016/j.tecto.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Stability of faults with heterogeneous friction properties and effective normal stress

Abstract: Abundant geological, seismological and experimental evidence of the heterogeneous structure of natural faults motivates the theoretical and computational study of the mechanical behavior of heterogeneous frictional interfaces. Fault zones are composed of a mixture of materials with contrasting strength, which may affect the spatial variability of seismic coupling, the location of high-frequency radiation and the diversity of slip behavior observed in natural faults. To develop a quantitative understanding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
136
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(142 citation statements)
references
References 66 publications
6
136
0
Order By: Relevance
“…Consistent with previous studies (e.g., Skarbek et al 2012;Dublanchet et al 2013;Luo and Ampuero 2017;Yabe and Ide 2017), we observed several different types of slip behavior in our parameter studies. The first is the "total seismic" regime, in which a mainshock event ruptures the entire seismogenic zone on the fault (parameter sets A-C in Fig.…”
Section: Seismic Cyclesupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with previous studies (e.g., Skarbek et al 2012;Dublanchet et al 2013;Luo and Ampuero 2017;Yabe and Ide 2017), we observed several different types of slip behavior in our parameter studies. The first is the "total seismic" regime, in which a mainshock event ruptures the entire seismogenic zone on the fault (parameter sets A-C in Fig.…”
Section: Seismic Cyclesupporting
confidence: 93%
“…Our results show that simple frictional heterogeneity on the fault can explain the variations in activity levels of precursory slip before large earthquakes, in addition to transitions in slip behavior (Skarbek et al 2012;Dublanchet et al 2013;Luo and Ampuero 2017;Yabe and Ide 2017) and seismicity between mainshocks. Because frictional parameters and effective normal stresses should vary both along strike and along dip, complex seismicity in subduction zones could be explained by variations in frictional parameters.…”
Section: Variations In Frictional Heterogeneity On the Plate Boundarymentioning
confidence: 73%
See 3 more Smart Citations